Mengulik Longevity Jasa Fotografi Di Tengah Gempuran Smartphone : Studi Kasus Pada Jasa Foto Hero Fotografi - Aulia Nurul Izza; Rauly Sijabat; Rita Meiriyanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Photography is one of the new avenues of service and business, some have made a hobby of photography a lucrative profession. They should be prepared to compete with other companies of the same kind by creating a good image of the consumer, providing quality of service and increasing innovation and creativity in order to create different photo concepts and attract consumers. The strategy became the main idea of Hero Photography to develop a business in photographic services. Hero Photography tried to adapt and compensate by coming up with a strategy that would attract consumers.These research methods use descriptive qualitative, with the aim of providing an idea and an explanation as to how startegi services Hero Photography in the interest of consumers. The study uses primary data sources as data obtained from informers and secondary data from archive or documents, journals, and various archival files of Hero Photography. Data collection techniques through observation, interview and documentary. At verifying data data using triangulation of methods and source triangulation using data analysis techniques of reposing data, presenting data, and summarizing data.Research has shown that the concept of sustainable excellence is influenced by the quality of the product, in this case, a superior photograph of adequate human resources capable with an obvious market target. The performance of the sale of Hero Photography was influenced by a marketing strategy with a concept of 4P (Price, Place. Product, Product), among other things is photographic quality, aesthetic quality good photo quality in terms of aesthetically pleasing clients who are less likely to use hero photography services. Strategic places like the old city become the attraction of visitors to capture the moment. Promotion became a strategy by using social media asa tool for promotion and offering online photo services by viewing affordable prices as one of the preferred customers to use the Hero Photography photo service.